Structural Principles in Liquids and Glasses: Bottom-Up or Top-Down - Egami, Takeshi; Ryu, Chae Woo (Frontiers in Materials, 2022)
The conventional approach to elucidate the atomic structure of liquid and glass is to start with local structural units made of several atoms, and to add them up to form the global structure, the bottom-up approach. We propose to add an alternative top-down approach in which we start with a global high-temperature gas state and then apply interatomic potentials to all atoms at once. This causes collective density wave instability in all directions with the same wavelength. These two driving forces, local and global, are in competition and are mutually frustrated. The final structure is determined through the compromise of frustration between these two, which creates the medium-range-order. This even-handed approach on global and local potential energy landscapes explains the distinct natures of short-range order and medium-range order, and strong temperature dependence of various properties of liquid.